Evidence support the potential for climate-smart agriculture in Tanzania - Jones, Kristal; Nowak, Andreea C.; Berglund, Erika; Grinnell, Willow; Temu, Emmanuel; Paul, Birthe K.; Renwick, Leah L.R.; Steward, Peter R.; Rosenstock, Todd S.; Kimaro, Anthony A. (Elsevier, 2023)
National governments across Sub-Saharan Africa include climate-smart agriculture (CSA)—context-specific interventions that support resilience, productivity, and climate mitigation—in plans, policies, and strategies to jointly address climate change, agricultural production, and rural livelihood goals. This paper synthesizes the evidence on field-based CSA management practices generated through ten years of research led by the CGIAR in Tanzania. Results show consistent positive impacts of CSA on productivity, mixed impacts on resilience, short-term negative impacts on emissions intensity, and highly variable impacts on socioeconomic characteristics. Tanzania provides an example of how an agriculturally diverse country can use evidence of impacts, synergies, and tradeoffs to prioritize CSA activities for sustainable development.